2012
DOI: 10.1016/j.contraception.2011.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging and gynecological devices

Abstract: Background: Performing magnetic resonance imaging (MRI) on women with gynecological devices is a completely accepted practice. The goal of our review is to assess how safe it is to perform MRI on women using contraceptive implants or devices. Study Design: Literature review, searching in PubMed-Medline/Ovid for the following keywords: magnetic resonance imaging, intrauterine devices, Implanon® and Essure®. Results: Though plastic devices do not represent a contraindication to the use of the technique, those in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 15 publications
(33 reference statements)
0
1
0
1
Order By: Relevance
“…43 Several reports have shown that neither movement nor clinically significant heating was associated with the copper IUD when undergoing magnetic resonance imaging using equipment <3.0T. 44 While the MEC cautions against use of the levonorgestrel IUD (LNG IUD) in women with a history of breast cancer, several studies have assessed its efficacy in preventing endometrial polyps, hyperplasia, and cancer in breast cancer survivors taking tamoxifen. A Cochrane review of LNG IUD use among women with breast cancer on tamoxifen suggested that the method decreased the incidence of benign endometrial polyps, but available trials were too small to study prevention of hyperplasia, endometrial cancer, and breast cancer recurrence.…”
Section: Consideration Of Cancer Type and Comorbidities In Contraceptmentioning
confidence: 99%
“…43 Several reports have shown that neither movement nor clinically significant heating was associated with the copper IUD when undergoing magnetic resonance imaging using equipment <3.0T. 44 While the MEC cautions against use of the levonorgestrel IUD (LNG IUD) in women with a history of breast cancer, several studies have assessed its efficacy in preventing endometrial polyps, hyperplasia, and cancer in breast cancer survivors taking tamoxifen. A Cochrane review of LNG IUD use among women with breast cancer on tamoxifen suggested that the method decreased the incidence of benign endometrial polyps, but available trials were too small to study prevention of hyperplasia, endometrial cancer, and breast cancer recurrence.…”
Section: Consideration Of Cancer Type and Comorbidities In Contraceptmentioning
confidence: 99%
“…Werden Frauen im fertilen Alter wegen Begleiterkrankungen zu bildgebenden Untersuchungen mittels Mag netresonanztomografie (MRT, Kernspin) überwiesen, so ist dies bei liegendem Intrauterinsystem problemlos möglich. Eine sonographische Kontrolluntersuchung ist nicht erforderlich, da es durch die MRT-Untersuchung zu keiner Lageveränderung des IUS im Uterus kommt [75,76].…”
Section: Mrt-untersuchungen Bei Liegendem Intrauterinsystemunclassified